Code Mixing Used in Masterchef Indonesia Season 5 - Rahman Fadil; Diyah Iis Andriani (VELES Voices of English Language Education Society, 2021)
Sociolinguistic is the study of language within society. During their communication in the society, people have their own styles as they have different backgrounds and ethnics. Those differences make them able to mix their languages during their interaction, which is called as code mixing. Nowadays, code mixing becomes a phenomenon and is used by people around the world, including on the television programs. MasterChef Indonesia season 5 is one of the television programs where the speakers produce code mixing during their communication. This study aimed to identify the types of code mixing and analyze the factors that influence people to do code mixing in their interaction in that television program. The data of this study were Indonesian-English code mixing used during the conversations in MasterChef Indonesia Season 5. This study used a descriptive method, and the writers used the theory from Muysken (2000) in analyzing the types of code mixing. Additionally, Beardsmore’s theory (1982) was used to analyze the factors that cause people doing code mixing. Based on the data analysis, it was found that the dominant type of code mixing used in this program was the alternation type, and the factor that dominantly influenced people doing code mixing is vocabulary.